2018
DOI: 10.7150/ijms.25115
|View full text |Cite
|
Sign up to set email alerts
|

Activated Yes-Associated Protein Accelerates Cell Cycle, Inhibits Apoptosis, and Delays Senescence in Human Periodontal Ligament Stem Cells

Abstract: Objectives: To provide insight into the biological effects of activated Yes-associated protein (YAP) on the proliferation, apoptosis, and senescence of human periodontal ligament stem cells (h-PDLSCs).Methods: h-PDLSCs were isolated by the limiting dilution method, and their surface markers were quantified by flow cytometry. Enhanced green fluorescence protein (EGFP)-labeled lentiviral vector was used to activate YAP in h-PDLSCs, then qRT-PCR and Western blotting were used to evaluate the expression level of Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 42 publications
4
40
0
Order By: Relevance
“…Following increases in DNA accessiblity, expression of newly opened TEAD1/YAP1/SMAD target genes cement FMT transition by promoting fibrosis and a myofibroblast-like, ECM-secreting state. This model is supported by the synergy between TEAD1 motifs and NAD domains we report and reconciles conflicting reports that YAP1/TEAD1 inhibition can both prevent and promote senescence [125, 84, 126, 127]. Basically, the functional consequences of YAP1/TEAD1 inhibition will depend on the epigenetic organization of the cells used.…”
Section: Discussionsupporting
confidence: 87%
“…Following increases in DNA accessiblity, expression of newly opened TEAD1/YAP1/SMAD target genes cement FMT transition by promoting fibrosis and a myofibroblast-like, ECM-secreting state. This model is supported by the synergy between TEAD1 motifs and NAD domains we report and reconciles conflicting reports that YAP1/TEAD1 inhibition can both prevent and promote senescence [125, 84, 126, 127]. Basically, the functional consequences of YAP1/TEAD1 inhibition will depend on the epigenetic organization of the cells used.…”
Section: Discussionsupporting
confidence: 87%
“…The present mechanism of action study provided the first evidence supporting that GGOH-prevented MSC death from ZA cytotoxicity was at least partly mediated through Rho-dependent activation of YAP. Rho subfamily proteins and YAP have been shown to play important roles in viability, proliferation and stemness of MSCs [ 20 , 21 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The present results demonstrated that GGOH-mediated YAP activation reversed ZA-induced cell cycle arrest by stimulating cell cycle progression and promoting more cells to enter S phase and G2/M phase, as previously reported for the role of YAP in the induction of cell cycle progression in chondrocytes [ 53 ]. Moreover, YAP has been shown to stimulate proliferation and inhibit apoptosis of stem cells [ 21 , 22 ]. However, it is also possible that in this context, other downstream effectors of Rho can also mediate cell division and proliferation of MSCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a Hippo signaling transcriptional coactivator, YAP plays pivotal roles in MSCs fate and organ size control [134]. Jia et al discovered that activated YAP promotes proliferation, accelerates the cell cycle, inhibits apoptosis, and delays senescence in human PDLSCs [135]. Knockdown of YAP inhibits the proliferation activity and induces apoptosis of human PDLSCs with the involvement of the Hippo pathway and shows crosstalk with the Erk and Bcl-2 signaling pathways 7 Stem Cells International [136].…”
Section: Immunomodulatory Key Markersmentioning
confidence: 99%